The EAX mode of operation - Bellare M. (2014)
We propose a block-cipher mode of operation, EAX, for solving the problem of authenticated-encryption with associated-data (AEAD). Given a nonce N, a message M, and a header H, our mode protects the privacy of M and the authenticity of both M and H. Strings N, M, and H are arbitrary bit strings, and the mode uses 2[|M|/n] + [|H|/n] + [|N|/n] block-cipher calls when these strings are nonempty and n is the block length of the underlying block cipher. Among EAX's characteristics are that it is on-line (the length of a message isn't needed to begin processing it) and a fixed header can be pre-processed, effectively removing the per-message cost of binding it to the ciphertext. © International Association for Cryptologic Research 2004.